Power: the missing element in sustainable consumption and absolute reductions research and action. (20th September 2016) - Fuchs, Doris; Di Giulio, Antonietta; Glaab, Katharina; Lorek, Sylvia; Maniates, Michael; Princen, Thomas; Røpke, Inge
Abstract: In this essay, we aim to demonstrate the value of a power lens on consumption and absolute reductions. Specifically, we illuminate what we perceive to be a troublesome pattern of neglect of questions of power in research and action on sustainable consumption and absolute reductions. In pursuit of our objectives, we delineate how many of the informal and implicit "theories of social change" of scholars and activists in sustainable consumption and sustainable development fail to address power in a sufficiently explicit, comprehensive and differentiated manner and how that failure translates into insufficient understandings of the drivers of consumption and the potential for and barriers to absolute reductions. Second, we develop the contours of a power lens on sustainable consumption. Third, we illustrate the value of such a power lens, with a particular focus on the case of meat consumption.